DRIVING PERFORMANCE THROUGH POSITIVE LEADERSHIP - Ramdas, Sunil Kumar; Patrick, Harold Andrew (Journal of Positive Management, 2019)
This conceptual paper is an attempt to outline positive leadership and its sub-dimensions. Several progressive theories on positive leadership have observed that, the understanding, developmental process and implementation of positive leadership still remains largely under-researched by scholars from both the fi elds of leadership and positive psychology. Researchers have identifi ed that good job performance is strongly related to positive style of leadership. The aim of this article is to highlight varied concepts of positive leadership and its meaning. Positive leadership is bascially about respecting people with whom we work, recognising their competencies, contributions, and acknowledging the fact that they are our fi rst customer with whom we do business. It is also about how they shape optimisim as part of the organisational culture over time, formulate positive strategy, introduce positive organisational design and develop available talent using their strengths into potential human capital. Method: A descriptive methodology was adopted to explore the available literature. The paper presents the concepts of positive leadership, leadership theories that form part of the positive leadership style, approaches and dimensions to positive leadership. They are defi ned and equated along with similar relationships with other leadership theories or concepts such as transformational, authentic and servant leadership. Findings: The review of literature indicated many similiarities and associations between concepts of positive leadership and leadership behaviour styles. It also found strong relationship between positive leadership behaviour and outcomes such as performace, satisfaction, trust, empowerment, engagement and other critical behaviours that make organisations both eff ective and eff icient.